(untitled) (Praxis Educativa, 2012)
Learning is a complex process because acquiring new knowledge implies integrating new data to the previous thought structure which usually acts as a barrier. How can this be done that without deforming that structure? By transforming it? This transformation is never immediate; it is always the result of a process originating in the interaction between preexistent elements - the learner’s conceptions and information given by the learning situation. Someone learns when the conceptions in his/ her mind are "activated". Construction and deconstruction are two different faces in the same development process. New data must interfere with the learner’s thought system to guide It and to re-organize it. In spite of all this, learning is not just a cognitive process Affective, cognitive and meta-cognitive aspects are closely connected in a sociocultural context.